CuO assisted borate 1393B3 glass scaffold with enhanced mechanical performance and cytocompatibility: An In vitro study. (February 2021) - Ali, Akher; Singh, Bhisham N.; Yadav, Sushma; Ershad, Md; Singh, Satyendra K.; Mallick, Sarada P.; Pyare, Ram
Abstract: Herein, three dimensional porous 1393B3 borate-based glass (BBG) scaffold along with their CuO derivatives (C1BBG, C2BBG, and C3BBG) tailored with trabecular bones' architecture were prepared by melt-quench route followed by foam replica technique. The properties of 'CuO incorporated' scaffolds, as compared to 'as prepared' scaffold were analyzed by a series of In vitro investigations for enhancement in biological compatibility, bioactivity, and physicomechanical performances. The in vitro study demonstrates superior mechanochemical stability of CBBGs (CuO derived 1393B3) than the pure BBG, while causing no or minimal effect on bioactivity and cytocompatibility post CuO incorporation to the BBG. In fact, the biological compatibility examined through MTT, Live/Dead, and cell adhesion study using the L929 cell lines was enhanced in the CBBGs up to 1% CuO incorporated scaffolds (C1BBG and C2BBG) in most cases. However, the enhanced biological compatibility was observed in C1BBG in comparison to other BBGs. Thus, the CuO incorporation into BBG enhanced mechanochemical and biological performance without affecting the bioactivity of the scaffold; henceforth, CBBGs could be considered neo bone tissue regenerative biomaterials.